TRANSLATION SHIFT OF NOUN PHRASES IN ENGLISH-INDONESIAN TRANSLATION OF SONG LYRIC ENTITLED FIX YOU BY COLDPLAY - Khairunnas Nur Putranto; Syaid Hagung Buwono; Miyarti; Syella Ardani; Iin Inawati (PROJECT (Professional Journal of English Education), 2024)
Translation is the replacement of text in one language (SL) with equivalent text in another language (TL). Shifts are unavoidable throughout the translation process because many words and phrases move due to the various linguistic systems of the source and target languages. This study aims to examine the different forms of translation shifts and the most prevalent shift observed in English to Indonesian Song Lyric Titled Fix You by Coldplay at the noun phrase level. The research approach is classified as content analysis. The results of this study reveal that seventeen translation shifts occur in the translation of the song lyrics. According to the study's findings, the most common translation shift of a noun phrase in a song lyric is structure shift, followed by unit shift, level shift, and class shift. Meanwhile, the lyric does not mention the intra-system shift. This research is expected to provide insight into language training, particularly translating song lyrics, which can inform translation practices and contribute to the improvement of language skills.